If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -1) * 2 = 21 Reorder the terms: 3(-1 + 3x) * 2 = 21 Reorder the terms for easier multiplication: 3 * 2(-1 + 3x) = 21 Multiply 3 * 2 6(-1 + 3x) = 21 (-1 * 6 + 3x * 6) = 21 (-6 + 18x) = 21 Solving -6 + 18x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 18x = 21 + 6 Combine like terms: -6 + 6 = 0 0 + 18x = 21 + 6 18x = 21 + 6 Combine like terms: 21 + 6 = 27 18x = 27 Divide each side by '18'. x = 1.5 Simplifying x = 1.5
| =9-8x(7) | | x^2-x=3150 | | =9-8*(7) | | -2y-7=57 | | 5+7y-15=8x-6+3x | | ZQ=3a | | 2x+14=-34 | | 4b-17= | | t/3-2=10 | | 0.13/0.2 | | 20x+14=34 | | 6S+S=245 | | -20x+14=34 | | 5x+26=16 | | 15.3+h=1.3-h | | x=1/3x=8 | | 4x+2(3x-5)=5x+14-7x | | X-3=25-10 | | 3xy+x+y=0 | | 441.5+x=22 | | u+4.6=9.17 | | h=x^2-8ln-2 | | tan(2pi+x)= | | h(x)=x^2-8ln-2 | | 8x+19=-28-8x | | -2w+8=-56 | | 5p^2+6p+1=O | | (y+9)2*2-(y+5)2*2=28 | | -7u-46=31 | | h(t)=-16t^2+36t+5 | | Y-8=2/3x | | 6d+57=39 |